2018
DOI: 10.1177/2333392818771243
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety Among Patients on Chronic Opioid Therapy

Abstract: Background:Chronic noncancer pain (CNCP) and chronic opioid therapy (COT) commonly coexist with comorbid depression and anxiety. We investigated the prevalence of depression and anxiety and their correlates at the time of controlled substance agreement (CSA) enrollment among patients with CNCP and a history of depression or anxiety on COT.Methods:Retrospective analysis of 1066 patients in a Midwest primary care practice enrolled in CSAs for COT between May 9, 2013, and August 15, 2016. Patients with self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
4
7
0
Order By: Relevance
“…Furthermore, PHQ -9 and GAD-7 appears to be a reliable and valid instrument that can be used to diagnose major depression (18.5%) and anxiety (15.2%) among Turkish women. This is consistent the with prevalence rate of major depression and anxiety observed rates 15.4% and 14.4% in United States among women (Elrashidi et al, 2018), also similarly study reported for the depression 14.7%, and anxiety 10.1% conducted in Latvia women (Ivanovs et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, PHQ -9 and GAD-7 appears to be a reliable and valid instrument that can be used to diagnose major depression (18.5%) and anxiety (15.2%) among Turkish women. This is consistent the with prevalence rate of major depression and anxiety observed rates 15.4% and 14.4% in United States among women (Elrashidi et al, 2018), also similarly study reported for the depression 14.7%, and anxiety 10.1% conducted in Latvia women (Ivanovs et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…30 For perspective, a recent study reported that among chronic non-cancer pain patients (n = 785) undergoing chronic opioid therapy, 14.6% screened positive for MDD utilizing the PHQ-9 and cut points applied by the current study. 28 Consistent with our findings, literature shows females as more prone to MDD. 12,17,22,23,30 A systematic review of depressive prevalence among university students identified only one study where males exhibited greater risk.…”
Section: Discussionsupporting
confidence: 92%
“…The PHQ-9 is a screening and diagnostic instrument for MDD, widely utilized in both clinical and research settings. 27,28 The PHQ-9 consists of 9 items each addressing specific symptoms of depression. The patient indicates whether they have been subject to any of the stated symptoms of depression over a period of the past two weeks.…”
Section: Depressive Symptomatologymentioning
confidence: 99%
“…Our results were similar to those of others. [24][25][26][27][28][29] The results of path analysis showed that family function has a signi cant impact on trait anxiety, and the path coe cient is 0.434 in male and 0.271 in female. Because the better the family function is, the lower the FAD-18 score is, and the higher the anxiety degree is, the higher the ST-AI score is.…”
Section: The Results Inmentioning
confidence: 99%